Akibat Hukum atas Pelanggaran Kewajiban Calon Notaris Magang: Studi Peraturan Perundang-Undangan - Fitria Rosalinda; Aminah Aminah (CV. Social Politic Genius (SIGn), 2023)
This study examines and analyzes the legal consequences of violations of obligations committed by prospective intern Notaries based on Law Number 30 of 2004 and Law Number 2 of 2014. This study uses normative legal research with the statute and conceptual approaches. The collected legal material is then qualitatively analyzed to describe the problem and answer study purposes. The results show that the Article 16A of Law Number 2 of 2014 prescriptively indicates that prospective intern Notaries have attributive authority in doing authentic deeds. On the other hand, it reveals no additional articles providing sanctions if a prospective intern Notary violates this Article 16A of Law Number 2 of 2014. Despite these conditions, prospective intern Notaries ignoring their obligations are not exempt from legal consequences under Article 444 section (1) of Law Number 1 of 2023, Article 1365 of the Civil Code, and Article 12 point 3 of INI Regulation Number 19/PERKUM/INI/2019. Therefore, it is recommended that all stakeholders, including prospective intern Notary and Notary accepting intern, strictly adhere to the legal and regulatory framework governing internships. Further, the House of Representatives could consider for Amendment to Law Number 30 of 2004. In this case, legislation formation must provide more explicit provisions on the limitations and responsibilities of prospective intern Notaries and the consequences of violations. Clarifying these aspects could prevent misunderstandings, enhance the effectiveness of the internship program, and ultimately improve the overall quality and integrity of the Notary profession.